Intelligent emotion recognition for drivers using model-level multimodal fusion - Luan, Xing; Wen, Quan; Hang, Bo (Frontiers in Physics, 2025)
Unstable emotions are considered to be an important factor contributing to traffic accidents. The probability of accidents can be reduced if emotional anomalies of drivers can be quickly identified and intervened. In this paper, we present a multimodal emotion recognition model, MHLT, which performs model-level fusion through an attentional mechanism. By integrating video and audio modalities, the accuracy of emotion recognition is significantly improved. And the model performs better in predicting emotion intensity, a driver emotion recognition dimension, than traditional results that focus more on emotion, recognition classification.